2020
DOI: 10.1002/ijgo.13294
|View full text |Cite
|
Sign up to set email alerts
|

Normative references and clinical correlates of fetal umbilical artery Doppler indices in southwestern Nigeria

Abstract: Objective To derive normative references for umbilical artery (UA) Doppler indices, including pulsatility index (PI), resistance index (RI), and systolic/diastolic (SD) ratio, for singleton pregnancies in Ile‐Ife, Nigeria, and compare them with reference values from other populations. Methods A longitudinal study involving 415 women with a singleton fetus at 26–40 gestational weeks attending Obafemi Awolowo University Hospital, Ile‐Ife, between July 2015 and March 2019. Fetal UA PI, RI, and SD ratio were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…With respect to obstetric outcomes, the prematurity rate is comparable with the report for the general obstetric population. The Caesarean section rate was comparable to the 47% reported from an earlier study, and the mean birth weight was also comparable to the 3210±490 g reported by Awowole et al from the same centre 3 years earlier 15. Hepatitis B infection in pregnancy was not associated with increased stillbirth or perinatal mortality rate among the cohort in this study, as the findings were comparable to the stillbirth rate of 15/1000 births recorded by Kuti et al among unselected booked patients at the same facility 16.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With respect to obstetric outcomes, the prematurity rate is comparable with the report for the general obstetric population. The Caesarean section rate was comparable to the 47% reported from an earlier study, and the mean birth weight was also comparable to the 3210±490 g reported by Awowole et al from the same centre 3 years earlier 15. Hepatitis B infection in pregnancy was not associated with increased stillbirth or perinatal mortality rate among the cohort in this study, as the findings were comparable to the stillbirth rate of 15/1000 births recorded by Kuti et al among unselected booked patients at the same facility 16.…”
Section: Discussionsupporting
confidence: 88%
“…The Caesarean section rate was comparable to the 47% reported from an earlier study, and the mean birth weight was also comparable to the 3210±490 g reported by Awowole et al from the same centre 3 years earlier. 15 Hepatitis B infection in pregnancy was not associated with increased stillbirth or perinatal mortality rate among the cohort in this study, as the findings were comparable to the stillbirth rate of 15/1000 births recorded by Kuti et al among unselected booked patients at the same facility. 16 The perinatal mortality rate of 29.2/1000 births from this study, though high, is comparable to the perinatal mortality rate of 38/1000 births reported by the Nigerian Demographic and Health Survey for the southwest geopolitical zone, where the OAUTHC is situated.…”
Section: Discussionsupporting
confidence: 88%
“…A total of 10 articles met the inclusion criteria which were used to assess the methodological quality at predefined criteria. [39][40][41][42][43][44][45][46][47][48] Mean score of all the research articles included in the current study was 49.7% (95%, CI, 45.1-54.1%). For the study design along with statistics used and the way of reporting, the quality assessment mean scores were 45.7 (95% CI, 40.9-50.4%) and 52.6% (95% CI, 47.1-58%), respectively.…”
Section: Resultsmentioning
confidence: 77%